STATUS HUKUM BAYI TABUNG (Kajian Hukum dan Status Keperdataanya) - Haniyah Haniyah; Uji Santoso (JURNAL LEGISIA, 2022)
The fact that not all couples can reproduce normally, some of them have various obstacles that do not denythem to have children, thisis why when the baby is not present, various efforts will be made by the married couple. Pesatnya in the field oftheologyof theology of married couples seeks to have offspring in one way, namely using technology fertilisasi in virto (IVF). This article discusses the legal status of IVF in its civil and legal perspective in Islam. IVF / artificial insemination if done with the wife's own sperm and ovum cells and is not transferred in the womb of other women including her own other wives (for polygamous husbands), both making is done in the Womb and outside the womb, then civil law and Islamic law are allowed, and regarding the child she gives birth to both civilly and Islamic shari'a is a legal child. IVF / artificial insemination is carried out with the help of sperm and egg donors, so islamic sharia is forbidden and the law is the same as adultery because there will be a mixture of nasab, while civilly Indonesia is also not allowed because it violates the norms of law, religion, decency and also decency. Artificial insemination is carried out with donors, be it from sperm cells or eggs, then to know the nasab of the child is determined from Islamic law, that the child's nasab comes from the mother / father who owns the seed, while in Indonesian civil the child is legally the mother who gave birth to the child and the father is the husband of the wife who gave birth to the child